Estudo de mecanismos de patogenicidade utilizados pela Salmonella enterica sorotipo typhimurium e Salmonella enterica sorotipo typhi no intestino de modelos animais de infecção - Luciana Fachini da Costa (2015)
Salmonellosis is one of the most important foodbourne diseases, and it is caused by Salmonella enterica, a Gram negative bacterium belonging to the Enterobacteriaceae family. S. enterica infection in humans may cause non-typhoidal salmonellosis, characterized by enteritis with severe neutrophilic infiltration, and it is caused mostly by S. enterica serotypes Typhimurium and Enteritidis, or typhoid fever, which is characterized by systemic dissemination of serotypes Typhi, Paratyphi and A, B, or C. The goals of this study were to assess distinct pathogenic mechanisms of S. Typhimurium and S. Typhi in the intestine of animal models of infection. Mechanisms by which S. Typhimurium uptakes ferrous and ferric iron in the inflamed intestinal environment were evaluated. There were utilized streptomycin pre-treated mice, mice treated with 3% DSS, and bovine ligated ileal loops models In mice pretreated with streptomycin and treated with 3% DSS, co-infections with reference strain and one of the mutants tonB feoB, feoB, tonB or iroN indicated that absorption of ferric iron mediated by IroN and TonB provides competitive advantage to S. Typhimurium in the inflamed intestinal environment. In addition, mechanisms by which S. typhi represses inflammation in the intestine were investigated. Insertion of tviA, regulatory Vi capsular gene of S. Typhi, into the genome of S. typhimurium did not alter the invasion rate of S. typhimurium but resulted in decreased fluid accumulation and inflammation in the bovine ligated ileal loop model. In these studies, animal models have proven to be important tools for assessment of pathogenic mechanisms of both S. Typhimurium and S. Typhi in the intestinal environment.